To investigate the effects of artemisinin on inflammatory factors and intestinal microbiota in rats with ulcerative colitis based on network pharmacology - Guo, Yuxi; Li, Ze; Cheng, Nan; Jia, Xuemei; Wang, Jie; Ma, Hongyu; Zhao, Runyuan; Li, Bolin; Cai, Yanru; Yang, Qian (Frontiers in Gastroenterology, 2022)
Abstract: Methods: Then, 40 male Wistar rats were randomly divided into normal group, model group, mesalamine group (0.315 g/kg·d) and artemisinin group (0.1 g/kg·d), with 10 rats in each group. Except for the normal group, the rats in the other groups drank 3.5% DSS solution freely for 10 days to replicate the UC model. After the successful modeling, the rats were given intragastric administration. The normal group and the model group were given the same amount of 0.9% normal saline, once a day. Dosing for 14 days. The general condition of the rats was recorded every day, and the disease activity index (DAI) score was performed. After the administration, the colonic mucosal damage index (CMDI) was scored, the histopathological changes of the colon were observed by HE staining, and the levels or activities of serum CRP, TNF-α, MDA, SOD, HIF-1α and T-AOC were detected by ELISA. , 16S rDNA sequencing technology to detect changes in rat fecal intestinal flora. Results: There were 98 key targets of artemisinin after screening, 4853 effective targets of UC, 43 intersection targets of artemisinin and UC, involving 48 signaling pathways. Molecular docking results showed that the binding energies of key proteins and artemisinin were all less than -5.0 kJ·mol-1, and the binding energy of PTGS2 and NOS3 to artemisinin was the best.Compared with the model group, the DAI and CMDI scores of the artemisinin group and the mesalazine group decreased, the levels and activities of serum CRP, TNF-α, MDA and HIF-1α decreased, the levels and activities of SOD and T-AOC increased, and the intestinal tract increased. The abundance and diversity of tract flora increased, p-Acidobacteria , p-Chloroflexi, p-Gemmatimonadetes, p-Nitrospirae abundance increased (P ＜0.05), and the rest had no significant changes.